2021
DOI: 10.3390/biology10060506
|View full text |Cite
|
Sign up to set email alerts
|

A New Application in Biology Education: Development and Implementation of Arduino-Supported STEM Activities

Abstract: Considering that generations that have grown up in the 21st-century have grown alongside technology, it is thought that integrating technology into lessons helps students learn the subject. This study aims to develop five STEM activities for the lesson of the human body systems by integrating the coding-based Arduino into STEM education. The activities were implemented to 6th-grade students for seven weeks and the effects on students’ skills of establishing a cause-effect relationship. The study method was pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The results of the analysis conducted are learning models that utilize the Conservation Science and Technology Identity Instrument (CSTI) as an empirical way to measure STEM identity (Rodriguez, et al, 2020). In addition, the use of technology including using the adruino application in STEM-based learning improves students' ability to establish cause and effect relationships (Görgülü Arı & Meço, 2021). STEM-based learning is also very suitable to be combined with the use of online application technology (Brunelli & Macirella, 2021).…”
Section: Implementation Of Stem-based Learning Models and Media In An...mentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the analysis conducted are learning models that utilize the Conservation Science and Technology Identity Instrument (CSTI) as an empirical way to measure STEM identity (Rodriguez, et al, 2020). In addition, the use of technology including using the adruino application in STEM-based learning improves students' ability to establish cause and effect relationships (Görgülü Arı & Meço, 2021). STEM-based learning is also very suitable to be combined with the use of online application technology (Brunelli & Macirella, 2021).…”
Section: Implementation Of Stem-based Learning Models and Media In An...mentioning
confidence: 99%
“…Therefore, equipping students with the ability to establish cause-effect relationships is an issue that teachers should add to their agenda (Görgülü Arı & Meço, 2021). STEM-based learning is known to improve students' HOTS skills (Yaki, 2022).…”
Section: Potential For Hots Improvement Through Stem Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding knowledge comprehension, research demonstrated the usefulness of Arduino and 3D printing in teaching STEM concepts in educational robotics classes (Souza & Sato, 2019). Regarding skills and competencies, it was found that integrating Arduino into STEM activities improved students' skills in establishing cause-effect relationships (Arı & Meço, 2021). Similarly, Vexler et al, (2022) developed an interdisciplinary course on circuit design using Arduino, which enhanced students' scientific and technological capabilities (Vexler et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Exploratory learning is thought to be a powerful way of introducing children to computer science concepts. The authors in [37] have discussed how exploratory learning using sensors supports STEM (science, technology, engineering, and mathematics) skills around the world. Since the beginning of the twenty-first century, the use of sensors has often been regarded as a powerful strategy in science and mathematics education that has contributed to improved learning outcomes [38] and teachers' positive experiences in science teaching [39].…”
Section: Educational Aspects Of Sensor Datamentioning
confidence: 99%